Kesadaran Masyarakat Dalam Pengembangan Kawasan Wisata Pantai Lakeba Kota Baubau - Jaelani; Tajuddin, Rosmala; Nuria, Ade (Universitas Muslim Buton, 2023)
Tourism development is one of the efforts to advance and develop tourist attraction objects into positive things in order to improve people's welfare in an economic sense. The purpose of this study was to determine public awareness in the development of the Lakeba beach tourism area in Baubau City. The method in this study uses a descriptive qualitative approach by making coastal communities as research subjects. Sources of data from this study were in the form of direct observation techniques, interviews and documentation to obtain data related to public awareness in the development of Lakeba Beach tourism in Baubau City. The results of this study concluded that public awareness in the development of the Lakeba beach tourism area has not been maximized due to the lack of government involvement in the development of the beach tourism area. Keywords: Awareness, Community, Development of Coastal Tourism Areas